Bovine veneral vibriosis: cure of genital infection in females by systemic immunization. - Schurig, G G (1975)
Cure of female cattle with venereal vibriosis by systemic immunization with killed Campylobacter fetus cells in incomplete Freund adjuvant was investigated. Heifers infected in the cervicovaginal area with a cloned population of C. fetus venerealis were vaccinated subcutaneously 14 and 24 days thereafter with the infecting strain in incomplete Freund adjuvant. Six of eight vaccinated heifers were free of infection 25 to 48 days postinfection. One of the cured animals had an intercurrent infection which precluded interpretation of a vaccine effect. All controls remained infected 48 to 51 days postinfection, when the experiment was terminated. In vaccinated animals, agglutination titers against whole cells of the infecting strain reached peaks varying from 1,280 to 20,480 in serum and from 20 to 5,120 in cervicovaginal mucus (CVM) within days 24 to 32 postinfection. No consistent relationship was noted between levels of whole cell antibodies in serum and those in CVM. Evidence for the occurrence of antigenic variation in the organism after vaccination was sought by comparing the agglutinability of the infecting strain and CVM isolates in serum and CVM extracts. Serum samples of most cured heifers agglutinated whole cells prepared from isolates of the respective heifers to the same extent as cells of the infecting strain. In the corresponding comparisons, those from noncured animals agglutinated isolates to lower titers. CVM extracts from one cured animals agglutinated isolates derived from the same or closely spaced CVM samples to titers comparable with those obtained with the infecting strain. In the remaining animals, CVM extracts which agglutinated the infecting strain produced lower or undetectable reactions with corresponding isolates. It is proposed that the elimination of infection is dependent upon opposing responses of host and parasite, of which the degree of antigenic alteration in the infecting strain and the rate of mobilization and the concentration of specific antibodies in the genital secretions are key factors.